2009
DOI: 10.1097/prs.0b013e3181b03787
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of Autologous Lymph Node Transplantation as Treatment of Postsurgical Lymphedema

Abstract: The successful reimplantation of a lymph node into a nodal excision site has the potential to restore lymphatic function and facilitate edema resolution. This result has important conceptual implications in the treatment of postsurgical lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 29 publications
3
59
1
Order By: Relevance
“…and non-superiority of one technique leaves most experts to regard these procedures as experimental, thus warranting further investigation [13,18]. Consequently, the mainstay of lymphedema management today largely consists of conservative modalities including manual lymphatic drainage, exercise, pneumatic pumps, and compression bandage therapy.…”
Section: Journal Of Aesthetic and Reconstructive Surgery Issn 2472-1905mentioning
confidence: 99%
See 1 more Smart Citation
“…and non-superiority of one technique leaves most experts to regard these procedures as experimental, thus warranting further investigation [13,18]. Consequently, the mainstay of lymphedema management today largely consists of conservative modalities including manual lymphatic drainage, exercise, pneumatic pumps, and compression bandage therapy.…”
Section: Journal Of Aesthetic and Reconstructive Surgery Issn 2472-1905mentioning
confidence: 99%
“…The mean limb volume was reduced by 57% in the experimental group treated with VLNT versus 18% in the non-surgical control group. Additionally, the rate of infection significantly decreased in the surgically treated group [13,14]. Most recently, a systematic review of 18 studies and 305 patients undergoing VLNT reported improved quality of life in all patients, with 91% improvement of limb circumference, 86% with reduced limb volume, and 60% with improved lymphatic flow [15][16][17][18].…”
Section: Vlntmentioning
confidence: 99%
“…Direct healing of transplanted lymphatics has been shown to occur in animal models and in vivo in transplanted free flaps and likely accounts for some of the improvements observed and the success found by those using recipient sites such as the wrist or ankle. 34,38,39 The main disadvantage of the VLNT procedure is the potential but unlikely risk for donor site morbidity. Careful selection and collection of lymphatics during the procedure is used to minimize risk of disturbing lymphatics at the donor site.…”
Section: Vascularized Lymph Node Transfer (Vlnt)mentioning
confidence: 99%
“…13 Lymphatic function 8 to 12 weeks after transfer was significantly higher in the vascularized group. Similarly, postoperative edema was less in the vascularized versus avascular lymph node transfer group; however, it failed to register significance.…”
Section: Experimental Studiesmentioning
confidence: 96%